Respuesta :

z = (kx^2)/y -> 3 = (k(2^2))/(4) -> k=3
z = (3*4^2)/9 = 16/3

Answer:

Joint variation says that:

If y varies directly to x and inversely to w then, the equation is of the form:

[tex]y = k \cdot \frac{x}{w}[/tex] where, k is the constant of variation.

As per the statement:

z varies directly with [tex]x^2[/tex] and inversely with y

By definition of joint variation:

[tex]z = k \cdot \frac{x^2}{y}[/tex]          ......[1]

When  x = 2 and y = 4, z = 3.

Solve for k:

Substitute the given values in [1] we have;

 [tex]3 = k \cdot \frac{2^2}{4}[/tex]

⇒[tex]3 = k \cdot \frac{4}{4}[/tex]

Simplify:

3 = k

or

k = 3

Then, an equation we get;

[tex]z = 3 \cdot \frac{x^2}{y}[/tex]

Substitute the value x =4 and y = 9 to solve for z:

[tex]z = 3 \cdot \frac{4^2}{9} = 3 \cdot \frac{16}{9} = \frac{16}{3}[/tex]

⇒The value of [tex]z = \frac{16}{3}[/tex]